Pengembangan Media Permainan Ludo Berbasis Self-Management untuk Mengurangi Prokrastinasi Akademik Siswa SMA PAB 11 Lubuk Pakam - Nazwa Azzahra; Muhammad Putra Dinata Saragi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
Academic procrastination is a common problem among senior high school students that can negatively affect academic achievement and psychological well-being. One factor contributing to this behavior is low Self-Management ability, while guidance and counseling (BK) services at SMA PAB 11 Lubuk Pakam have mainly relied on conventional methods that provide limited active student engagement. This study aims to describe the development of Self-Management-based Ludo game media using the 4D model, determine its feasibility based on expert assessments, and evaluate its practicality based on BK teacher and student responses. This Research and Development (R&D) study employed the 4D model consisting of Define, Design, Develop, and Disseminate. Needs data were collected from 13 eleventh-grade students, while product feasibility was assessed by a BK content expert and a learning media expert. A limited trial involved four students. The results showed a needs analysis mean score of 3.22 (64.4%, High). Content expert validation obtained a mean score of 4.83 (96.7%, Very Good), while media expert validation obtained 3.79 (75.7%, Good), with a combined mean of 4.31 (Very Good). Practicality testing resulted in an 86.2% BK teacher response and a 91.25% student response. Thus, the Self-Management-based Ludo game media is feasible and practical as an innovative and interactive group BK medium for helping students reduce academic procrastination.